2018
DOI: 10.1016/j.jep.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Increase in insulin sensitivity by the association of chicoric acid and chlorogenic acid contained in a natural chicoric acid extract (NCRAE) of chicory (Cichorium intybus L.) for an antidiabetic effect

Abstract: Increase in insulin sensitivity by the association of chicoric acid and chlorogenic acid contained in a natural chicoric acid extract (NCRAE) of chicory (Cichorium intybus L.) for an antidiabetic effect, Journal of Ethnopharmacology, https://doi.org/10. 1016/j.jep.2017.12.035 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…Among the differentially perturbed B. pilosa metabolites were HCA derivatives, identified as significant ions in response to treatment with either elicitor. In previous studies, these groups of secondary metabolites were reported to have various health benefits such as anti-cancer properties [ 50 ], HIV-integrase inhibition by 3,5-di-caffeoylquinic acid [ 51 ] and chicoric acid [ 52 ] and anti-diabetic properties [ 53 , 54 ]. In this study, the di-caffeoylquinic acids, the 4,5-, 3,4- and 3,5- geometric isomers exhibited similar distribution profiles, prominent in the MeJA_12 and the MeSA_24 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Among the differentially perturbed B. pilosa metabolites were HCA derivatives, identified as significant ions in response to treatment with either elicitor. In previous studies, these groups of secondary metabolites were reported to have various health benefits such as anti-cancer properties [ 50 ], HIV-integrase inhibition by 3,5-di-caffeoylquinic acid [ 51 ] and chicoric acid [ 52 ] and anti-diabetic properties [ 53 , 54 ]. In this study, the di-caffeoylquinic acids, the 4,5-, 3,4- and 3,5- geometric isomers exhibited similar distribution profiles, prominent in the MeJA_12 and the MeSA_24 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…CA is produced in plants in the shikimic acid pathway during aerobic respiration. This compound is an ingredient, not only in foods, but also in traditional Chinese medicine preparations [4,5]. In the latter, it has been found to exert hypoglycemic [6,7], hypolipidemic [8], antibacterial [9], antioxidant [10], and anti-inflammatory [11] effects.…”
Section: Introductionmentioning
confidence: 99%
“…So, the trend towards using traditional herbal medicinal products is continuously increasing Ethanolic extracts of leaves of Annona muricata showed antidiabetic actions which might be due to the presence of many potential antioxidative phytocompounds like chlorogenic and caffeic acids, procyanidins (epi)catechin, quercetin and kaempferol (Justino et al, 2018). In streptozotocin induced diabetic rats, chicoric acid derived from roots of Cichorium intybus causes a significant reduction in basal hyperglycemic conditions with improvisation of oral glucose tolerance due to its ability to scavenge free radicals like H2O2 (Ferrare et al, 2018). Entagenic acid, an aglycone present in seed kernels of E. phaseoloides possess a significant antidiabetic effect in type 2 diabetic mice by activation of downstresm AMP-activated protein kinase – Glucose Transporter (AMPK/GLUT4) pathway (Xiong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%